PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN - Haryatih, Haryatih (Akuntabilitas, 2024)
This study aims to determine the effect of Profitability, Liquidity and Leverage on Company Value in mining companies listed on the Indonesia Stock Exchange in 2018- 2022. The variables tested in this study consisted of profitability which was proxied by Return On Equity (ROE), Liquidity proxied by Current Ratio (CR), and Leverage proxied by Debt to Equity Ratio (DER) as independent variables and Company Value which was proxied by Price to Book Value (PBV) as the dependent variable. The sampling technique used in this study was purposive sampling and obtained a sample of 60 data from 12 mining companies listed on the Indonesia Stock Exchange in the period 2018-2022 that met certain criteria. In this study the data analysis technique used is panel data regression analysis with the help of statistical software Eviews version 9. The results of this research show that profitability has a positive and significant effect on firm value, liquidity has a negative but not significant effect on firm value, leverage has an effect negative but not significant to Company Value and Profitability, Liquidity and Leverage together have a simultaneous and significant effect on Company Value.